2015
DOI: 10.3390/en81012304
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CO2 Bubble Size, CO2 Flow Rate and Calcium Source on the Size and Specific Surface Area of CaCO3 Particles

Abstract: Abstract:The effects of CO2 flow rate and calcium source on the particle size (PS) and specific surface area (SSA) of CaCO3 particles were evaluated using microbubble generator (MBG) and air diffuser (AD) systems. The carbonate mineralization (CM) and precipitated calcium carbonate (PCC) methods were employed to produce CaCO3 using gypsum and Ca(OH)2 as the calcium sources, respectively. The CaCO3 particles prepared using the MBG were smaller (with larger specific surface area) than those obtained using the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The primary particle size of the CaCO3 also gradually increased with an increase of the CO2 flow rate at a low Ca(OH)2 concentration, but the tendency became weak at high Ca(OH)2 concentration. They also revealed that the CO2 bubble size also affected the particle size and specific surface area (Bang et al, 2015).…”
Section: Effect Of Other Factors On the Formation Of Caco3 Polymorphsmentioning
confidence: 99%
“…The primary particle size of the CaCO3 also gradually increased with an increase of the CO2 flow rate at a low Ca(OH)2 concentration, but the tendency became weak at high Ca(OH)2 concentration. They also revealed that the CO2 bubble size also affected the particle size and specific surface area (Bang et al, 2015).…”
Section: Effect Of Other Factors On the Formation Of Caco3 Polymorphsmentioning
confidence: 99%
“…A jacket reactor was used for CO2 mineralization, with a coolant at 1 °C being circulated between the walls by a chiller, and a lid being placed on the upper part of the reactor. As CO2 microbubbles were injected into the suspension using a microbubble generator, the pH decreased rapidly, as has already been shown in the literature [7,26,27]. CO2 injection was stopped once the pH of the brine had decreased to 8.…”
Section: Methodsmentioning
confidence: 87%
“…In addition, even though the CaCO3 precipitate consisted of a large amount of Mn, Mn-doped crystals (e.g., Mn·Ca(CO3)2) or MnCO3 was not formed in the three CaCO3 crystal phases. The CaCO3 obtained herein can be utilized as an industrial material, e.g., as a paper-making filler, because the shape and size distribution of the obtained CaCO3 herein can enhance the smoothness of paper surfaces, as well as printing quality [36]. Other metal ions, such as Mg, Al, and Ti were not supposed to form crystalline minerals.…”
Section: Co 2 Mineralization Of Ca Leached From Bfsmentioning
confidence: 97%